2021
DOI: 10.1075/jslp.20024.kan
|View full text |Cite
|
Sign up to set email alerts
|

The interplay of proficiency and study abroad experience on the prosody of L2 speech acts

Abstract: Adopting Brazil’s (1997) prosodic framework, this study examined whether proficiency and study abroad experience impact second language (L2) English learners’ spoken production of speech acts. Twenty-four native English speakers and 64 Japanese learners of L2 English participated in the study. The L2 learner group was divided into three sub-groups: (1) high proficiency learners with study abroad (SA) experience (2) low proficiency learners with no SA experience, and (3) high proficiency learners without SA exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
5
1
Order By: Relevance
“…In Kang et al's (2021b) study on imposition and speech acts, the use of level tone was used more by NSs and high proficiency learners with study abroad experience. This stands in contrast to low level learners in their study who tended to use more rising tones in high imposition speech acts (requests and opinions) which can be considered inappropriate for the situation (Kang et al, 2021b). Therefore, in high-imposition refusals, it appears that BLs were relying more strategically on level tones, similar to NSs and other high proficiency learners reported in Kang et al (2021b).…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…In Kang et al's (2021b) study on imposition and speech acts, the use of level tone was used more by NSs and high proficiency learners with study abroad experience. This stands in contrast to low level learners in their study who tended to use more rising tones in high imposition speech acts (requests and opinions) which can be considered inappropriate for the situation (Kang et al, 2021b). Therefore, in high-imposition refusals, it appears that BLs were relying more strategically on level tones, similar to NSs and other high proficiency learners reported in Kang et al (2021b).…”
Section: Discussioncontrasting
confidence: 58%
“…Prosody plays a crucial role in both creating and disambiguating meaning (Culpeper, 2011). While much prosodic research has been concerned with differences in how the prosody of NSs and NNSs influences accentedness, comprehensibility, or intelligibility, recent research has been focusing on how prosodic differences also convey pragmatic meaning (Kang & Kermad, 2019;Kang, Kermad, & Taguchi, 2021b;Kermad, 2021). One way this occurs is through intonation.…”
Section: The Pragmatics Of Prosodymentioning
confidence: 99%
See 1 more Smart Citation
“…However, intra-language study is the least researched topic and only takes up 3.2%. The type that is studied most among three types of comparative study of request is interlanguage (Kang et al, 2021;Siddiqa & Whyte, 2021), while intra-language type (Schoppa, 2022) is studied least.…”
Section: Results Of Three Categories Of Comparative Study Of Requestmentioning
confidence: 99%
“…Correspondingly, L2 learners' use of prosody has become an important area of investigation when conceptualizing their pragmatic competence. Empirical results from L2 English studies have revealed that learners use prosodic features (intonation and fluency) in a certain way when producing speech acts and that the use often indicates their level of pragmatic competence and development (Kang et al, 2021;Kostromitina, in press;Li, 2014;Taguchi, 2012;Taguchi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%